1990
DOI: 10.1080/1120009x.1990.11739028
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Epithelial Ovarian Cancer: No Difference in Survival Rate Between Exploratory Laparotomy and Inadequate Debulking Surgery as Treatment Approach before Chemotherapy

Abstract: In this study we have retrospectively evaluated 40 untreated patients with stage III-IV (FIGO) epithelial ovarian cancer. Sixteen patients had received, as initial treatment, inadequate surgical removal of the tumor with bulky residue (BR) of disease and 24 had had an exploratory laparotomy (EL) only. Subsequently, both groups received equivalent chemotherapy consisting of AC combination (adriamycin, cyclophosphamide) in 25 patients. Following surgery plus chemotherapy the two groups achieved a similar high re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Unlike Bristow and Chi, they excluded studies that reported survival data among the NACT responders only and not the entire cohort of NACT patients [62,63,70,74]. Also, in contrast to Bristow and Chi, two studies were excluded because they did not report the exact median overall survival [47,89] and in one study, the authors performed NACT followed by second look operation only without ICS [90]. Kang and Nam also included seven additional studies that were performed since Bristow and Chi published their meta-analysis.…”
Section: Meta-analysismentioning
confidence: 92%
“…Unlike Bristow and Chi, they excluded studies that reported survival data among the NACT responders only and not the entire cohort of NACT patients [62,63,70,74]. Also, in contrast to Bristow and Chi, two studies were excluded because they did not report the exact median overall survival [47,89] and in one study, the authors performed NACT followed by second look operation only without ICS [90]. Kang and Nam also included seven additional studies that were performed since Bristow and Chi published their meta-analysis.…”
Section: Meta-analysismentioning
confidence: 92%
“…From several retrospective phase II studies, it appears that the outcome of these women, treated with neoadjuvant chemotherapy followed by interval debulking surgery, is essentially the same as for patients treated with primary debulking surgery followed by chemotherapy. These studies are summarized in Table 2 (21,36–59) . In most of these studies, interval debulking surgery was performed after three or four courses of neoadjuvant chemotherapy.…”
Section: Neoadjuvant Chemotherapy and Interval Debulking Surgerymentioning
confidence: 99%
“…Table 1. Patient characteristics of the randomized EORTC (34) and GOG 152 (35) (36) 24 NAC increase the chances of optimal debulking Lawton et al (37) 36 78% IDS of which 89% ,2 cm Tummarello et al (38) 24 NAC could be a valid alternative to surgery Jacob et al (39) 22 Same survival as 18 matched controls Lim and Green (40) 30 NAC can make patients operable Shimizu and Hasumi (41) 74 46% IDS to ,2 cm…”
Section: Neoadjuvant Chemotherapy Followed By Interval Debulking Surgmentioning
confidence: 99%